Identification of signaling pathways modifying human dopaminergic neuron development using a pluripotent stem cell-based high-throughput screening automated system: purinergic pathways as a proof-of-principle - Boissart, Claire; Lasbareilles, Marie; Tournois, Johana; Chatrousse, Laure; Poullion, Thifaine; Benchoua, Alexandra (Frontiers in Pharmacology, 2023)
Perturbation of the development, maturation and projection of dopaminergic neurons has been proposed to contribute to several devastating neurological and psychiatric disorders. Understanding the signals modulating the genesis of human dopaminergic neurons is therefore crucial to elucidate disease etiology and identify counteracting measures to prevent them. In this study, we developed a screening model based on human pluripotent stem cells to identify modulators of dopaminergic neuron genesis. We set up a protocol of differentiation allowing to obtained floorplate midbrain progenitors competent to produce dopaminergic neurons and cultivated them into 384 well screening plates in a fully automated manner. This allowed treating these progenitors with collections of small molecules in order to identify compounds increasing dopaminergic neurons production. As a proof of principle, we screened a library of compounds targeting purine and adenosine dependent pathways. We identified an agonist of adenosine receptor 3 as a candidate molecule increasing dopaminergic neuron genesis in physiological conditions as well as in a model of Lesch-Nyhan disease. This screening model offers the opportunity to identify therapeutic molecules for a variety of disease affecting dopaminergic circuit development and plasticity at large throughput and to improve our knowledge of the etiology of these diseases.